The Influence Of Clinical Skills and Supervision Techniques On the Implementation Of Patient Safety Standards With Caring Behavior as An Intervening Variable in Inpatient Nurses at Rsau Soemitro - Dwi Yanti Elok Palupi; Kemala Rita; Nofierni Nofierni; Rokiah Kusumapradja (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
The implementation of patient safety standards is a major challenge in healthcare services, particularly in hospitals such as RSAU Soemitro. Data indicates that there were 25 patient safety incidents in the Inpatient Installation in 2023, with falls being the most common case (9), followed by nosocomial infections, medication errors (4), and the absence of patient identification bracelets during surgery (7). This study aims to analyze the influence of clinical skills and supervisory techniques on the implementation of patient safety standards at RSAU Soemitro, with caring behavior as an intervening variable. This quantitative research employs a cross-sectional study design, using a sample of 110 nurses in the inpatient installation. Data collection was conducted using questionnaires, and data analysis was performed using SEM-PLS techniques. The results show that the implementation of patient safety standards is simultaneously influenced by clinical skills, supervisory techniques, and caring behavior. Caring behavior can be significantly influenced by both clinical skills and supervisory techniques. Additionally, the implementation of patient safety standards is influenced by clinical skills and supervisory techniques both directly and indirectly through caring behavior. Furthermore, caring behavior has been proven to be the most significant factor, contributing 53.1%. These findings suggest that hospital management should focus on interpersonal skills training to support better implementation of patient safety standards.